Dakwah Dalam Bingkai Politik - Hamzah Khaeriyah (TASAMUH: Jurnal Studi Islam, 2018)
In the condition of being Indonesia context, the relationship between preaching and politic could be seen in three views. Firstly, accommodative group stated that spiritual life is arranged by religion and secular life is arranged by secular logic. So that, these are necessary attempt to separate between preaching and politic. Secondly, moderate group gives opinion that Islam is not only to understand as a religion but as an ideology. Islam is totalistic religion (kaffah) that arranges all life aspects of society including in social-politic life. Thirdly, idealist-radical groups stated that Islam is there on all ideologies, so that to sacrifice is required the hardness ways and concurrently refused ideology of five principles as the one and only foundation as society organization of social life and that religion must be as ideology to change the five principles of Indonesia. In perspective of al-Qur’an, politic wished to be preaching philosophy as a reference, having the positive goal so that allow becoming politic as preaching media. Preaching through politic wished can arrange the society with the base of behavior of al-karimah, to unite the society with attitude brotherhood and affection. Be able to uphold the justice, wellbeing and mutual assistance. To uphold the leadership serves to community necessity, arranging the society with the fair law and beneficial progression. Thus, be able to understand that preaching in politic frame should apply on the underlayment of morality and to pay attention of politic ethic